Divided attention costs for speeded and non-speeded movements to near and far targets - Hart, M. A.; Dornier, L. A.; Reeve, T. G. (Journal of Human Movement Studies, 2006)
Research has shovvn that reaction times to a primary task are slovved vvhen paired vvith speeded and non-speeded second tasks. The non-speeded effect has been attributed to attentional demands. However, an additional explanation for the non-speeded effect may be due to programming demands. The purpose of the present experiments was to examine both attentional and programming demands as explanations for the non-speeded effect. The first experiment examined the influence of speeded and non-speeded second tasks on the reaction times for a primary task. The second experiment examined the influence of thc accuracy demands of a second task on the reaction times for a primary task. The results suggest that the non-speeded effect may be attributed to both programming and attentional demands.